2022
DOI: 10.1038/s41598-022-09329-z
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonic bone age fractionates cognitive abilities in adolescence

Abstract: Adolescent development is not only shaped by the mere passing of time and accumulating experience, but it also depends on pubertal timing and the cascade of maturational processes orchestrated by gonadal hormones. Although individual variability in puberty onset confounds adolescent studies, it has not been efficiently controlled for. Here we introduce ultrasonic bone age assessment to estimate biological maturity and disentangle the independent effects of chronological and biological age on adolescent cogniti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 84 publications
0
12
0
Order By: Relevance
“…We were also particularly interested in those potential windows of vulnerability that are suggested by the earlier mentioned brain maturational processes, e.g., cortical pruning, late frontolimbic maturation ( Hwang et al, 2016 ; Marek et al, 2018 ; Yang & Tseng, 2021 ) and neurotransmitter imbalance (for a review see Pitzer, 2019 ). To this end, we assessed the biological age of both GS and VS adolescent males assuming that biological age as assessed by bone age will be in correlation with brain maturation ( Kovács et al, 2022 ). We found that VS males are significantly more mature than GS males.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We were also particularly interested in those potential windows of vulnerability that are suggested by the earlier mentioned brain maturational processes, e.g., cortical pruning, late frontolimbic maturation ( Hwang et al, 2016 ; Marek et al, 2018 ; Yang & Tseng, 2021 ) and neurotransmitter imbalance (for a review see Pitzer, 2019 ). To this end, we assessed the biological age of both GS and VS adolescent males assuming that biological age as assessed by bone age will be in correlation with brain maturation ( Kovács et al, 2022 ). We found that VS males are significantly more mature than GS males.…”
Section: Discussionmentioning
confidence: 99%
“…The same experimenter performed all the bone age assessments with the same device. The device estimates bone age (in years and months) by measuring the speed of sound and the distance between the transducers, using algorithms based on gender and ethnicity (see the detailed description of the method in Kovács et al, 2022 ).…”
Section: Methodsmentioning
confidence: 99%
“…88.52% of mothers and 83.61% of fathers of adolescent participants had a university degree demonstrating high socioeconomic status among the participating families. The EEG data collection was part of a large-scale study, within which each adolescent participant was also administered the Wechsler Intelligence Scale for Children, 4th edition (WISC-IV) 34 , carried out a fine motor task 36 , and a Stroop test 35 .…”
Section: Participantsmentioning
confidence: 99%
“…Recently, we have introduced ultrasonic bone age as a promising alternative for maturity assessments in human developmental research 42 , with evidence for selective maturity-dependent effects in cognitive 42, 43 , motor 44 , and emotional development 45 . Operating without harmful radiation, this technology gauges acoustic conductivity at hand and wrist growth zones ( Fig.…”
mentioning
confidence: 99%
“…Their ndings suggest that pubertal maturation plays a signi cant role in the effectiveness of generating cognitive control responses. In a previous study 32 , we investigated the independent effects of chronological age and bone age (determined through ultrasonic assessment) on working memory and other cognitive abilities in female adolescents. The results clearly indicated that bone age, re ecting maturation, had a selective effect on working memory.…”
Section: Introductionmentioning
confidence: 99%